The influence of cultivation temperature on some phenotypic traits of Yersinia pseudotuberculosis (One Health & Risk Management, 2020)
Introduction. Some causative agents of sapro-zoonotic infections can multiply in the external environment (water reservoirs, soils, plants), as well as in animals, including microorganisms of the genus Yersinia.Material and methods. Isolation and identification of Y. pseudotuberculosis was carried out in accordance with the instructions on “Epidemiology, laboratory diagnosis of yersiniosis, organization and conduct of preventive and anti-epidemiological measures”. Antibiotic sensitivity was performed via the disc diffusion method in accordance with EUCAST and national guidelines. Biofilm formation was tested using the spectrophotometric assay.Results. It was established that the studied cultures showed a decrease in the level of saccharolytic activity during cultivation at a temperature of +37°C in comparison with the results obtained at 25°C, changes in sensitivity to antibiotics depending on the temperature of cultivation were revealed. It was established that Y. pseudotuberculosis cultures were able to form denser (λ 570) biofilms when cultured at 25°C, in comparison with biofilms formed at 37°C.Conclusions. Biological characteristics of the studied Y. pseudotuberculosis isolates (changes in the saccharolytic activity, the level of sensitivity to antibiotics and the formation of biofilms were revealed) depends on the cultivation conditions.